2009
DOI: 10.3758/app.71.8.1941
|View full text |Cite
|
Sign up to set email alerts
|

A heuristic model of sensory adaptation

Abstract: Adaptation is a universal process in organisms as diverse as bacteria and humans, and across the various senses. This article proposes a simple, heuristic, mathematical model containing tonic and phasic processes. The model demonstrates properties not commonly associated with adaptation, such as increased sensitivity to changes, range shifting, and phase lead. Changes in only four parameters permit the model to predict empirical psychophysical data from different senses. The relatively prolonged time courses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…(for reviews, see Kumar et al, 2004Kumar et al, , 2009). Imaging and neurobiological research has shown that chronic alcohol consumption can lead to white matter degradation, disrupt neurocircuitry, and impact neural plasticity which can alter neurotransmission, particularly by increasing tonic inhibition (Cardenas et al, 2005;Crews et al, 2005;Herting et al, 2010;McBurney and Balaban, 2009;Oscar-Berman and Marinkovic, 2007;Pfefferbaum et al, 2010;Santhakumar et al, 2007;Sullivan and Pfefferbaum, 2005). Particularly relevant to the collegeaged population, high doses of adolescent ethanol exposure has been shown to produce lasting changes in functional brain activity (for review, see Ehlers and Criado, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…(for reviews, see Kumar et al, 2004Kumar et al, , 2009). Imaging and neurobiological research has shown that chronic alcohol consumption can lead to white matter degradation, disrupt neurocircuitry, and impact neural plasticity which can alter neurotransmission, particularly by increasing tonic inhibition (Cardenas et al, 2005;Crews et al, 2005;Herting et al, 2010;McBurney and Balaban, 2009;Oscar-Berman and Marinkovic, 2007;Pfefferbaum et al, 2010;Santhakumar et al, 2007;Sullivan and Pfefferbaum, 2005). Particularly relevant to the collegeaged population, high doses of adolescent ethanol exposure has been shown to produce lasting changes in functional brain activity (for review, see Ehlers and Criado, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…In this review, adaptation is defined broadly, as “adjustment” ( 1 , 21 ). An adaptation level or “normal level” exists for all sensory dimensions including perception of frequency and intensity of stimuli ( 1 ).…”
Section: Individualmentioning
confidence: 99%
“…Adaptation level effects and similar “differential contextual effects” (Marks and Arieh, 2006 ) have been demonstrated in perception of: touch, taste, olfaction (Marks and Arieh, 2006 ), pain (Rollman, 1979 ; Kyle et al, 2009 ), weight (Helson, 1948 ), temperature (Masuyama, 1994 ), loudness (Marks, 1994 ), vision (Helson, 1964 ), phobias (Lauterbach, 1979 ), and even market research (Della Bitta and Monroe, 1974 ). There are a number of overlapping terms to describe change in perception with repeated exposure including acclimatization, adaptation, stimulus failure, fatigue as well as habituation (Helson, 1964 ; Mazess, 1975 ; McBurney and Balaban, 2009 ). The use of the terms are often governed by the training of the author, for example, adaptation is often used in physiology to describe a change, possibly short-term, in the response of sensory systems following stimulation, habituation is a decrease in response after repeated stimulation, sensitization an increase in response with repeated stimulation.…”
Section: Adaptation Level Theorymentioning
confidence: 99%